PostIndependentzia - Calzada, I (Translokal Academic Entrepreneurship SL, 2014)
Postindependence is the day after independence but also the management of all of the strategic processes that need to be prepared beforehand, and the management of the governance of the plebiscite/referendum onwards. PostIndependence is to be understood per se as Independence, as a process or way rather than as a goal. Independence is not a black and white issue, and cannot be taken into account without its content. Thus, PostIndependence is an amalgamation of the knowledge and practice that we need in order to bring about the right to decide without previous determinism. In order to put this right to decide into practice we should prepare a future scenario that consists of a series of territorial policies and strategies. Following on from there, we ought to, starting today, prepare for, research, agree upon, work on, and disseminate these policies and strategies throughout the society. This future strategic scenario from today is, thus, what PostIndependence is all about. #BeingThereWeAreHere is an essential leveraging effect, a mantra, or a tool that helps build the transition towards this future strategic scenario from today called PostIndependence. In order to start setting the scenario for PostIndependence, this notion has to be progressively developed in a systematic, effective, democratic, serious, and strategic manner. It should consist of a permeable and fruitful ongoing relationship with people internationally in order to join together the external with the internal, and reverse. We should ban the word “overseas”. On the other hand, we should understand that there ought to be a permanent nexus and exchange between the international community and the Basque Country with the ongoing #BeingThereWeAreHere as our mantra or slogan. The Basque writer Bernardo Atxaga coined the literary metaphor ‘Euskal Hiria’ (understood as an inclusive city-regional configuration of the Basque territory) to challenge us to imagine the natural path by which we would be able to work out our inner contradictions. This remains an unfinished business, an imaginary unachieved and thus a reality unresolved. We have not materialised the metaphor and fully come to terms with the diverse and socially complex nature of the Basque geographies. Quarrelling and short-sightedness remain the daily rule in Basque politics, and dealing with this provokes a mess entangled in a contradiction that paralyses any forward-looking attempt at strategic policy-makings. While Atxaga might not have succedded in this attempt, however, Joseba Sarrionandia, another prominent and still highly relevant Basque writer from the same generation as Atxaga, may have managed to show the way some time ago, when he suggested the TransLoKal mantra, #BeingThereIAmHere. A territory where the inner and outer dynamics have merged together has contradictions that should be faced and accepted, contradictions that are equally ours, one's own, and lived by others. In the age of globalisation, what is the role that ‘Basqueness’ should play? Or, alternatively, what should be the contribution of ‘Basqueness’ to the world at large? Moreover, how can a contemporary internationally constructed Basqueness be fixed to keep up and stay relevant to the challenges that lay ahead? This issue becomes one of goals and methods alike. Which TransLoKal territorial strategy should be pursued? Should it be pursued through networking among individuals in a self-established hybrid merger of local and global territorial locations? What is the role of the official Basque institutions regarding their current work and contribution to the TransLoKal entrepreneurial aim as a way to promote the Basqueness abroad? And is it possible for us, when defining territorial strategies and policies at the local level, to turn the role of social entrepreneurs and activists into promoters of progress rather than victims of stagnation? This core idea of this book is that the Basque Country, due to its own intricacies rather than merely as a consequence of its being kidnapped and held captive by the old-fashioned Spanish and French state legal frameworks, has come, over the years, to develop many points of inertia that are inherent in its territorial policies and strategies. In short, this work starts from the thesis that the territory, the people, the imaginary, indeed Basqueness itself has now reached a turning point. The Basque geographies are at a clear strategic crossroads. As Keating has argued (2001, 2005, 2009), globalisation and European integration have led to a resurgence of post-nationalism, beyond that of the nation-states. Territories are making their way forward, but not every route is the same. This is why the contribution of social innovation is essential, so that we can strategically research, observe and prepare these democratic processes. Here, therefore, the Basque Country is compared with the seven other City-Region territories that make up the focus of research in the project http://www.cityregions.org: Catalonia (Spain), Dublin (Ireland), Iceland, Liverpool/Manchester (UK), Oresund (Sweden and Denmark), Portland (Oregon) and Scotland (UK). Each of the territories studied has its own peculiarities as well as its own strategy and policies. The goal here is to relativise the Basque Country and then look to an understanding of how Basque Country is conceived in these other territories rather than by the administrative hindrances and institutional confines of Spain and France. How is the Basque Country seen from the outside? And how can that inform our own route? Looking forward, what exactly is to be done? It is clear that the world and also the Basque Country, is at a threshold of new geopolitics and a novel geostrategy, so how might we take advantage of the opportunity to become in a national community with an internationally perspective? A variety of factors inform the possible new TransLoKal territorial strategies. These include, among others, the ending of ETA's activities, political normalisation and opportunities for a peace process; the failure of the socio-economic and territorial model of the Spanish state and the need for a new constitutional order; the ageing of the nation-state model, real administrative division and the emergence of city-regions as urban-based geographical units; the importance of migration movements of all kinds (socio-economic and political, intraregional and transnational, etc.); very specifically, the perpetuation of the inertia of cultural politics rooted to the decimononic medieval ground of feuding Oinaz and Gamboa clans, and very generally, the need for a socially balanced post-crisis economic model. All of the above should be material for formulating questions about the territoriality of the Basque Country. We should avoid the temptation to provide theoretical answers, however, and should rather strive to introduce into our society a democratic policy-making and its realisation in action. The Basque Country, it is argued, requires a new kind of political culture based on building bridges and finding agreements between diverse positions. This is characterised as a rationalised dialectic working toward an original contemporary, city-regional and local/global PostIndenpendentist politics. Indeed, the other researched territories mentioned are all city-regions in the sense that they are developing territorial strategies and policies in order to work out their right to determine their own territorial subjectivity. The Basque Country should prepare its democratic process with the highest degree of social innovation possible by comparing with other territories instead of going it alone. This is why the book is called PostIndependence, in reference to a future scenario, to the right to decide for this hypothetical independent territory of tomorrow and the need to prepare, research, implement and disseminate territorial strategies and policies. Implicitly, it is assumed and accepted that the independence or devolution processes (OECD, 2001) are essentially democratic processes, as shown by some of the EU cases and elsewhere around the world. However, in this preparatory work, it is vital that other territories should be observed, linked, compared and benchmarked. Indeed, the transnational identity of the Basque Country should be constructed relatively in connection with others rather than be based solely on self-identification. In the period ahead, the Basque will need to work on its recognition, including from other territories, TransLoKal strategies and policies will be crucial here. Firstly, international territorial issues should be addressed by systemically merging them with internal territorial issues; and secondly, TransLoKal entrepreneurs - meaning enterprising indivuals, social activits and progressive small organizations - should be given a leading role, without, that is, having to depend on the blind and burdensome dominance of traditional institutions and their management structures. Entrepreneurs must go before, with the support and coordination of institutions. This is actually the opposite of what is happening: institutions are smothering the initiative of the few entrepreneurs and social activists and bringing everything to a halt, thereby dampening dynamism, blocking social transformation and encumbering the system overall. #BeingThereWeAreHere is a tool to gradually prepare the future scenario for PostIndependence in a serious, systematic and strategic way in order to gather strength from within and withough. Otherwise, provisional acts lacking prospective could leave the territorial development in an exposed, aimless position. The Basque system needs a stimulus in which public institutions, private firms, academia, technological centres, trade unions, social and economic agents, civil society and individuals (entrepreneurs/activists) are all included. Structurally, the book is divided into two sections. The book aims to be an entrepreneurial essay. That is to say, on the one hand, it begins with free narrative style presented entirely from a personal point of view but informed by an academic systematic, systematic rigour, and it concludes with a comparative and prospective proposal, which is the main contribution. Overall, it is proposed as operational outcome the platform www.PostIndependence.org in order to self-manage these communities on- and offline. The first section, entitled #BeingThereIAmHere (a quotation from Joseba Sarrionandia), offers a personal and experiential essay style. The guiding principle is clear: what is territory and what Basque territoriality would be like in a forthcoming geopolitical, geostrategic, and TransLoKal context. In the second section, entitled #BeingThereWeAreHere, the author puts aside his personal position and takes on the role of researcher in presenting a scientific and entrepreneurial academic essay. Rather than providing a prescriptive work and a recipe of answers to be applied, the goal is to foster discussion by identifying questions that may lead towards policy-making projects. Special effort has been made to open up the way towards having a solid and rigorous discussion. This section is sub-divided up into four subsections - Maps, Names (& Beings), Territories, and Strategies – each of which, in turn, is further divided into four parts. The goal is to reach the PostIndependence section first by explaining and then by working through in reverse order, the following parts: Critical Social Innovation, Smart City, We (& The Others) (comparison with the seven territories), City-Regions, Communities and TransLoKal.